Models and Variables of the Enterprise Digital Transformation - Schwer, Karlheinz; Hnilica, Jiří, 1976-; Dvořáček, Jiří, 1947-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
As the digital transformation success or failure of companies increasingly determines the life and death of companies, it is becoming increasingly important for companies to be able to assess their digital transformation capabilities, to know the most important variables in the game of digital transformation. Furthermore, this thesis is about how companies need to invest to be able to implement digitization projects and be financially successful. Because the speed of digitization plays a decisive existential role, the thesis looks at which organizational forms are best suited for digitization. In the thesis, 147 variables for digital transformation are identified within the framework of a literature analysis and assigned to an enterprise architecture scheme. For this purpose, the databases Scopus, EBSCO - Business Source Premier and ProQuest were evaluated in a structured manner using a keyword search. By assigning variables to enterprise architecture levels, companies can find and understand the relevant variables depending on the enterprise architecture level where they have the strongest pressure to change. They can prioritize the selected variables for their company, and optimize the most important variables in their operations according to the prioritization. The fifteen digital maturity models found include variables for the enterprise architecture levels: Strategy, Business, Applications, Technology. There are no variables in the maturity models for the physical layer and the implementation and migration layer of the architecture model. Furthermore, a broad database with relevant variables about enterprise investments of the European Investment Bank is analyzed. The correlations and regression coefficients of several enterprise finance variables and the digital transformation activities as well as the company’s financial success are measured.
It thus becomes clearer which characteristics companies have that are very actively digitizing and at the same time are financially very successful. The findings help companies to focus on the identified investment aspects to be more digitally active and financially successful than other companies. In addition, the aim is to show which organizational forms are suitable for digitization when and at what point in the company life cycle. Particularly in rapidly changing times, new organizational models such as Holacracy offer a prerequisite for quickly improving in the digital capabilities that are important for a company. Companies therefore gain insight here into which direction they need to develop their organization for which phase of the corporate lifecycle to remain competitive. The organizational models of the classic line organization, matrix organization and Holacracy are examined and shown how they function in the digitalized world.
Vedoucí práce: Jiří Hnilica
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations